Measurements of boil-off gas and stratification in cryogenic liquid nitrogen with implications for the storage and transport of liquefied natural gas. (1st May 2021) - Perez, Fernando; Al Ghafri, Saif Z.S.; Gallagher, Liam; Siahvashi, Arman; Ryu, Yonghee; Kim, Sungwoo; Kim, Sung Gyu; Johns, Michael L.; May, Eric F.
Abstract: The boil-off gas (BOG) produced from liquefied natural gas (LNG) mixtures in cryogenic storage tanks must be predicted reliably as a function of tank shape, heat ingress, thermal stratification, pressure, and liquid volume fraction. However, current methods of estimating BOG rates for large-scale tanks are entirely empirical and based on limited available data, with no models available for reliable predictions. This affects the ability of LNG carriers to optimise BOG compressor sizing. A new apparatus was developed to explore the effects of heat flux, liquid stratification, volume, and mixture composition on the measured boil-off rate. The apparatus is demonstrated using liquid nitrogen with BOG rates quantified as a function of various heat fluxes, pressures, and initial liquid volume fractions. Three distinct periods of boil-off were observed: the pressurisation, transient, and steady-state stages. The data are compared with the available literature and the predictions of a new dynamic model accounting for heat transfer from the super-heated vapour. Excellent agreement is observed between model predictions and the data measured during the pressurisation and steady-state stages. However, the model does not capture the BOG rate observed in the transient stage, suggesting liquid thermal stratification should be considered in future models for LNG boil-off. Highlights: Unique apparatus providing comprehensive sets of data for cryogenic fluid boil-off. Boil-off-gas (BOG) measurements of LN2 conducted for various conditions. In-depth analysis of pressure build-up, thermal stratification and BOG rates. Three distinct periods of BOG: pressurisation, transient, and steady-state stages. A new robust model to predict the dynamic weathering of cryogenic fluids.